Vocational Training for Adolescents and Adults with Autism Spectrum Disorder: Effectiveness of the Practical Assessment Exploration System (PAES) (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2017)
There are few specific, validated vocational training programs for individuals with Autism Spectrum Disorder (ASD).  The Practical Assessment Exploration System (PAES) is a functional vocational skills training tool that teaches and measures vocational potential in individuals with developmental disabilities.  This project utilized a mixed methods approach to better understand the effectiveness of PAES in enhancing the vocational abilities of twelve adolescents and young adults with ASD.  Results indicate a statistically significant improvement in vocational skill and behaviour after completing PAES.  Additional qualitative interviews with parents and attendees highlight four primary themes: strengths, benefits derived, limitations, and program suggestions.  Implications of these findings are discussed.